2007
DOI: 10.1039/b615326g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different head groups and functionalised side chains on the cytotoxicity of ionic liquids

Abstract: To enlarge the restricted knowledge about the hazard potentials of ionic liquids to men and the environment we have concentrated on systematically analysing the effects of 7 head groups, 10 side chains (mainly containing functional groups) and 4 anions on cytotoxicity. For our investigations, we used the promyelotic leukemia rat cell line IPC-81 as test system, with the reduction of the WST-1 dye as an indicator of cell viability. Our results show that most of the tested 100 ionic liquids generally exhibit a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
188
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(199 citation statements)
references
References 33 publications
10
188
1
Order By: Relevance
“…There has been sufficient interest in the recent past on toxic effects of ionic liquids on microorganisms 24,27,28 and on mammalian cells. 22,25 We estimated the cytotoxicities of pyrridinium and piperidinium ionic liquids and they fall in the same range as imidazolium ionic liquids. 25,27 In addition, we observed that the toxicities of pyrridinium and piperidinium ionic liquids increase with an increase in the alkyl chain length, similar to that of imidazolium ionic liquids (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been sufficient interest in the recent past on toxic effects of ionic liquids on microorganisms 24,27,28 and on mammalian cells. 22,25 We estimated the cytotoxicities of pyrridinium and piperidinium ionic liquids and they fall in the same range as imidazolium ionic liquids. 25,27 In addition, we observed that the toxicities of pyrridinium and piperidinium ionic liquids increase with an increase in the alkyl chain length, similar to that of imidazolium ionic liquids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 We estimated the cytotoxicities of pyrridinium and piperidinium ionic liquids and they fall in the same range as imidazolium ionic liquids. 25,27 In addition, we observed that the toxicities of pyrridinium and piperidinium ionic liquids increase with an increase in the alkyl chain length, similar to that of imidazolium ionic liquids (Fig. 6b) [Br] -is twice as low as that for NaBr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their introduction into industrial processes, together with their organic character, motivated the first studies of their interaction with biomolecules and bio-organisms (Petkovic et al 2011). As a result, several studies have highlighted their toxicity on living organisms (Pretti et al 2006;Bernot et al 2005;Ranke et al 2006Ranke et al , 2007aStolte et al 2007;Kulacki and Lamberti 2008). Toxicity is also a measure of the high affinity between RTILs and biosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Although the negligible volatility of ILs is one appealing point in the use of ILs in place of volatile organic solvents, the finite solubility of ILs in water has raised concern in wastewater treatments and other circumstances. [169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187] Since ILs are salts having certain solubility in water, the interface between an IL and water is inevitably electrified. There are a number of systems in which the phase-boundary potential across the IL|W interface plays a crucial role in determining the physicochemical characteristics of the systems.…”
Section: Introductionmentioning
confidence: 99%